Decreased biofilm formation by planktonic cells of Listeria monocytogenes in the presence of sodium hypochlorite. (June 2021) - Bansal, Mohit; Dhowlaghar, Nitin; Nannapaneni, Ramakrishna; Kode, Divya; Chang, Sam; Sharma, Chander S.; McDaniel, Christopher; Kiess, Aaron
Abstract: The objective of this study was to determine if the adaptation at planktonic stage to subinhibitory concentrations (SIC) of sodium hypochlorite (NaOCl) could modulate the biofilm forming ability of five Listeria monocytogenes strains V7, Scott A, FSL-N1-227, FSL F6-154 and ATCC 19116 representing serotypes 1/2a, 4b and 4c. Biofilm formation by NaOCl nonadapted and adapted L. monocytogenes planktonic cells was measured in the presence or absence of SIC of NaOCl. The biofilm formation ability of NaOCl nonadapted and adapted L. monocyotgenes planktonic cells was reduced only in the presence of NaOCl ( P < 0.05). Scanning electron microscopy revealed that the continuous exposure of NaOCl induced morphological changes in the L. monocytogenes biofilm structure and reduced its attachment to polystyrene surface. The qRT-PCR results also showed that the subinhibitory NaOCl reduced biofilm formation related gene expression such as motility and quorum sensing signals ( P < 0.05). These findings indicate that subinhibitory NaOCl can reduce the ability of L. monocytogenes planktonic cells to form biofilms on polystyrene surface. Highlights: Subinhibitory NaOCl decreases biofilm forming ability of L. monocytogenes. NaOCl adaptation in planktonic cells does not change biofilm forming ability of Lm. SEM, TEM and qRT-PCR results confirmed the biofilm inhibitory effect of NaOCl.